Micropropagation of Arugula Plant (Eruca sativa Mill.) - ABDUL RAUF, Aisha; MEMON, AbdulRezzak; YILDIRIM, Mehmet Uğur (ISPEC Tarım Bilimleri Dergisi, 2024)
Tissue culture, an essential technique in modern plant biology, offers promising avenues for the mass production of elite plant varieties for desirable traits. This study compared the effects of 0.1 mg L-1 NAA- 0.25 mg L-1 BAP plant growth regulator combination using Cotyledon leaves (0.4 cm²) of three Eruca cultivars Estht 195, Estht 198, and Estht 201 of arugula (Eruca sativa Mill.) cultured for four and six weeks. Significant differences were noted among them for callus induction percentage, shoot induction percentage, and plant height (cm). Notably, var. Estht 201 indicated consistently improved performance, with a callus formation percentage of 61.83 % in 4 weeks and 74.05 % in 6 weeks. Similarly, Var. Estht 201 exhibited higher shoot induction (Week 4 67.45 %, Week 6:69.9 %), and plant height (Week 4:7.50 cm, Week 6:9.6 cm), throughout the experiment. These findings contributed to a deeper understanding of arugula micropropagation Dynamics. At the same time, this study has once again shown how important tissue culture micropropagation protocols are in terms of improving yield and quality as well as breeding studies.